Imprinted polymer and Cu2O-graphene oxide nanocomposite for the detection of disease biomarkers. (1st July 2021) - Nasrullah, Amara; Afzal, Adeel; Mujahid, Adnan; Lieberzeit, Peter; Bajwa, Sadia Zafar; Mustafa, Ghulam; Latif, Usman
Abstract: α 1 -Acid glycoprotein ( α 1 -AGp) is a critical plasma protein that acts as a biomarker for different diseases when produced in large amounts (>1.2 mg ml −1 ). Therefore, selective, label-free, and fast detection of α 1 -AGp in human serum is essential. This article presents the development of selective coatings based on molecularly imprinted polymer (MIP) matrix with boronate-affinity and Cu2 O-decorated reduced graphene oxide (Cu2 O-rGO) nanomaterials. The MIP-Cu2 O-rGO hybrid coatings are fabricated on quartz crystal microbalance (QCM) to develop biomimetic α 1 -AGp sensors. The MIP:Cu2 O-rGO ratio is optimized to enhance sensing properties. Thus-designed MIP-Cu2 O-rGO/QCM sensor performs sensitive and specific detection of α 1 -AGp in complex mixtures. The initial assessment of the MIP-Cu2 O-rGO/QCM sensor reveals an eight-fold increase in the response toward α 1 -AGp compared to non-imprinted polymer. The MIP-Cu2 O-rGO/QCM sensor exhibits high sensitivity (16.28 Hz ng −1 ml −1 ) and a low limit of detection (0.25 ng ml −1 ). When compared with multiple biorelevant analytes such as bovine serum albumin, lysozyme, glucose, fructose, and uric acid, the sensor shows high selectivity due to suitably oriented imprints or interaction sites that are tailored for α 1 -AGp recognition. Furthermore, the MIP-Cu2 O-rGO/QCM sensor can effectively detect 150–200 ng ml −1 of α 1 -AGp in spiked human serum samples with a recovery rate of ∼92%. The results achieved in this study are compared with the relevant literature. The MIP-Cu2 O-rGO/QCM sensor can be suitably used for the label-free, precise detection of α 1 -AGp in complex mixtures.